In situ polymerization of p-phenylenediamine on a bacterial cellulose matrix as a potential glucose biosensor - Gabryś, Tobiasz; Biniaś, Dorota (Chemical and Process Engineering: New Frontiers, 2026)
Bacterial cellulose (BC) is a biopolymer distinguished by its high purity, nanofibrillar structure, large specific surface area, and excellent mechanical and biocompatible properties, making it an attractive platform for biosensing applications. In this study, we report the in situ polymerization of p-phenylenediamine (PPD) on a bacterial cellulose matrix as a novel strategy for the fabrication of a functional composite material with potential biosensor applications. The polymerization process was carried out directly within the BC network, enabling uniform deposition and strong interfacial interactions between the polymer phase and the cellulose nanofibers. The resulting BC/PPD composite was characterized using spectroscopic, structural, and morphological analyses to confirm successful polymer formation and integration within the BC matrix. The modification led to noticeable changes in the physicochemical properties of bacterial cellulose, including enhanced electrical responsiveness and altered surface chemistry, which are critical parameters for sensor performance. Owing to the combination of BC’s porous architecture and the functional properties of poly(p-phenylenediamine), the developed composite demonstrates promising potential as a flexible, biocompatible sensing platform for future biosensor and bioelectronic applications.